Relation between warm-up with massage before competition and the result of the struggle and performance the boxers - Beyleroglu, M.; Kolayis, H.; Ramazanoglu, F.; Hazar, M.; Cenk, A.; Bajorek, W. (Archives of Budo, 2009)
Background and study aim: The massage before the competition and a short technical and tactical performance with a trainer make boxers ready for the exercises. Material and methods: The research was applied on boxers who fight during Samsun Turkey Senior championship between 05-10.12.2006 and during Sivas Turkey junior championship between 28.01-02.02.2007. 112 volunteer boxers whose average age is 19,62 ± 4,333 years, average weight is 66,45 ± 14,577 kg and average height is 171,65 ± 9,730 cm became a part of the study. The data gained during research verified electronically and statistically analysed using the Wilcoxon Signed Rank Test. Results: The result of this study shows that there is a significant difference between the results of the competition with reference to warm-up with massage and without massage. Conclusions: Noticed that the massage just before the competition provides vigour, flexibility, improve both concentration and easy movement, and is parallelly form of warm-up exercises in which boxer used less energy.